GERHANA DALAM NALAR TARJIH MUHAMMADIYAH : ANTARA SAINS DAN TRADISI MASYARAKAT - Purnamasari, Dian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
This article discusses the perspective of the Muhammadiyah Tarjih Council on the eclipse phenomenon, by placing it in an integrative framework between modern science and community traditions. In Muhammadiyah's view, an eclipse is not a bad omen as some traditional communities believe, but a natural event that can be explained scientifically as part of Allah's law (sunnatullah). Nevertheless, Muhammadiyah still emphasizes the importance of the spiritual dimension through the eclipse prayer as a form of cosmic awareness and human submission to God. With a normative legal approach, this article also explores how Muhammadiyah's tarjih approach seeks to enlighten the community through da'wah that is educative, rational, and remains sensitive to local culture. Using a qualitative-descriptive approach and normative analysis, this paper concludes that the eclipse in the view of tarjih Muhammadiyah is a meeting point between faith, science, and tradition, which represents a progressive style of Islam.